Leptin receptor expression in the dorsomedial hypothalamus stimulates breathing during NREM sleep in db/db mice. Issue 6 (24th February 2021) - Pho, Huy; Berger, Slava; Freire, Carla; Kim, Lenise J; Shin, Mi-Kyung; Streeter, Stone R; Hosamane, Nishitha; Cabassa, Meaghan E; Anokye-Danso, Frederick; Dergacheva, Olga; Amorim, Mateus R; Fleury-Curado, Thomaz; et al.
Abstract: Study Objectives: Obesity leads to obstructive sleep apnea (OSA), which is recurrent upper airway obstruction during sleep, and obesity hypoventilation syndrome (OHS), hypoventilation during sleep resulting in daytime hypercapnia. Impaired leptin signaling in the brain was implicated in both conditions, but mechanisms are unknown. We have previously shown that leptin stimulates breathing and treats OSA and OHS in leptin-deficient ob/ob mice and leptin-resistant diet-induced obese mice and that leptin's respiratory effects may occur in the dorsomedial hypothalamus (DMH). We hypothesized that leptin receptor LepR b -deficient db/db mice have obesity hypoventilation and that restoration of leptin signaling in the DMH will increase ventilation during sleep in these animals. Methods: We measured arterial blood gas in unanesthetized awake db/db mice. We subsequently infected these animals with Ad-LepR b or control Ad-mCherry virus into the DMH and measured ventilation during sleep as well as CO2 production after intracerebroventricular (ICV) infusions of phosphate-buffered saline or leptin. Results: Awake db/db mice had elevated CO2 levels in the arterial blood. Ad-LepR b infection resulted in LepR b expression in the DMH neurons in a similar fashion to wildtype mice. In LepR b - DMH db/db mice, ICV leptin shortened REM sleep and increased inspiratory flow, tidal volume, and minute ventilation during NREM sleep without any effect on the quality of NREM sleep or CO2 production. Leptin had no effect on upper airway obstruction in these animals. Conclusion: Leptin stimulates breathing and treats obesity hypoventilation acting on LepR b -positive neurons in the DMH.